Aplikasi Smartphone GIS (Geografik Information System) Pencarian Lapangan Futsal Daerah Tangerang Berbasis Android - Ekasari, Munich Heindari; Diana, Desy; Saefudin, Mohamad (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
Geographyc Information System (GIS) is an information system that is applied to store, recall, enter, analyze, process, and produce data in the form of geographic data, used for decision making in support of a system development plan. The problem of finding information to find out the location of various places in an area with the help of smart phones. The use of smart phones in a growing community, then the idea arose to create an application called Find Your Futsal, which is an application about futsal field information based on the Geographyc Information System in the Tangerang area. Futsal has many benefits for the surrounding community. They can use the futsal field to support various futsal activities. The design method of this GIS application research application uses the SDLC (System Development Life Cycle) research method. Started designing the displays in the application, designing the database used in making the application. Next start the application by coding with a predetermined programming language using the Android Studio application. Furthermore, it is compiled and implemented on Android-based mobile devices. The application of the results of this study is a geographic information system application futsal field in the city of Tangerang that is simple and easy to use. As well as GPS and maps as features in it.